2012
DOI: 10.1098/rsfs.2012.0009
|View full text |Cite
|
Sign up to set email alerts
|

Peptide- and saccharide-conjugated dendrimers for targeted drug delivery: a concise review

Abstract: Dendrimers comprise a category of branched materials with diverse functions that can be constructed with defined architectural and chemical structures. When decorated with bioactive ligands made of peptides and saccharides through peripheral chemical groups, dendrimer conjugates are turned into nanomaterials possessing attractive binding properties with the cognate receptors. At the cellular level, bioactive dendrimer conjugates can interact with cells with avidity and selectivity, and this function has partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
49
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 75 publications
(51 citation statements)
references
References 150 publications
(168 reference statements)
0
49
0
2
Order By: Relevance
“…conformation is usually strongly dependent on pH conditions), and surface functional groups that could possibly discriminate biological targets and enhance drug solubility. [44][45][46][47][48][49][50][51][52] The poly(amidoamine) (PAMAM) dendrimers are the first and most extensively studied family of dendrimers. [44] Figure 1b depicts the threedimensional structure of a model of a 4 th -generation PAMAM (G4-PAMAM).…”
Section: Introductionmentioning
confidence: 99%
“…conformation is usually strongly dependent on pH conditions), and surface functional groups that could possibly discriminate biological targets and enhance drug solubility. [44][45][46][47][48][49][50][51][52] The poly(amidoamine) (PAMAM) dendrimers are the first and most extensively studied family of dendrimers. [44] Figure 1b depicts the threedimensional structure of a model of a 4 th -generation PAMAM (G4-PAMAM).…”
Section: Introductionmentioning
confidence: 99%
“…The drop in zeta-potential of R9 dendrimer particles is probably due to the smaller N/P ratio required by this material (40 for R9 dendrimer vs. 60 for unmodified or TAT dendrimer). Though numbers of studies have reported the toxicity of cationic PAMAM [31], no adverse effect from tadpole dendrimers in metabolic activity was detected in primary cardiomyocytes by MTT (Supplemental Figure 2), implying decreased cytotoxicity after modification. These results are consistent with studies showing that reducing the charge on PAMAM via modification results in reduced toxicity [25, 32].…”
Section: Discussionmentioning
confidence: 99%
“…It has been found to exhibit several advantages such as controlled release of the drug at a target organ and reduction of side effect associated with the drug; it minimizes the access of the drug to normal organs, thereby reducing the toxic effects, and the drug concentration to the required organs can be increased without harmful effects on other organs. Different types of delivery carriers used in targeted drug delivery systems are dendrimers [21], liposomes [22], polymeric micelles [23], and biodegradable particles [24]. Presently few drug delivery systems have been developed which have potential for treatment of diabetes [25], cancer [26], heart diseases [27], and rheumatoid arthritis [28].…”
Section: Introductionmentioning
confidence: 99%